Approximation Theorems for Functions of Two Variables via σ-Convergence - Mohammed A. Alghamdi (Journal of Function Spaces)
Çakan et al. (2006) introduced the concept of σ-convergence for double sequences. In this work, we use this notion to prove the Korovkin-type approximation theorem for functions of two variables by using the test functions 1, x, y, and x2+y2 and construct an example by considering the Bernstein polynomials of two variables in support of our main result.